A novel therapeutic vaccine targeting the soluble TNFα receptor II to limit the progression of cardiovascular disease: AtheroVax™ - Iversen, Patrick L.; Kipshidze, Nicholas; Kipshidze, Nodar; Dangas, George; Ramacciotti, Eduardo; Kakabadze, Zurab; Fareed, Jawed (Frontiers in Cardiovascular Medicine, 2023)
The burden of atherosclerotic cardiovascular disease contributes to a large proportion of morbidity and mortality, globally. Vaccination against atherosclerosis has been proposed for over 20 years targeting different mediators of atherothrombosis, however, these have not been adequately evaluated in human clinical trials to assess safety and efficacy. Inflammation is a driver of atherosclerosis, but inflammatory mediators are essential components of the immune response. Only pathogenic forms of sTNFR2 are acted upon while preserving the membrane-bound (wild-type) TNFR2 contributions to a non-pathogenic immune response. We hypothesize that the inhibition of sTNRF2 will be more specific and offers long-term treatment options. Here we describe pre-clinical findings of an sTNFR2-targeting peptide vaccine (AtheroVax™) in a mouse model. The multiple pathways to synthesis of the soluble TNFRII receptor (sTNFRII) were identified as sTNFRII(PC), sTNFRII(Δ7), and sTNFRII(Δ7,9). The sTNFRII(Δ7) peptide, NH2-DFALPVEKPLCLQR-COOH is specific to sTNFR2 based on an mRNA splice-variant in which exon 6 is joined to exon 8. The role of sTNFRII(Δ7) as a mediator of prolonged TNFα activity by preventing degradation and clearance was investigated. Inflammation is a critical driver of onset, progression and expansion of atherosclerosis. The TNFα ligand represents a driver of inflammation that is mediated by a splice variant of TNFR2, referred to as sTNFRII(Δ7). The multiple forms of TNFRII, both membrane bound and soluble, are associated with distinctly different phenotypes. sTNFRII(PC) and sTNFRII(Δ7) are not equivalent to etanercept because they lack a clearance mechanism. The unique peptide associated with sTNFRII(Δ7) contains a linear B-cell epitope with amino acids from both exon 6 and exon 8 supporting the vaccine design. Animal studies to evaluate the vaccine are ongoing, and results will be forthcoming. We describe a peptide vaccine targeting sTNFR2 in limiting the progression of atherosclerosis. A therapeutic vaccine limiting the progression of atherosclerosis will greatly contribute to the reduction in morbidity and mortality from cardiovascular disease. It is likely the vaccine will be used in combination with the current standards of care and lifestyle modifications.